2020
DOI: 10.21203/rs.3.rs-99869/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Healthcare workers’ knowledge and attitudes towards COVID-19 in Saudi Arabia

Abstract: Background: The world is facing a devastating challenge in the COVID-19 (coronavirus disease 19) outbreak. Healthcare workers (HCWs) provide the first line of defense against any disease outbreak. Thus, the present study is designed to assess HCWs’ attitudes towards, knowledge of, and awareness of COVID-19. Methods: A cross-sectional observational study was conducted using an online survey on social media; the participants were 597 adults. The study was conducted from March to April, 2020. The questionnaire wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 13 publications
3
16
1
Order By: Relevance
“…However, a higher proportion of HCWs perceived a high risk of COVID-19 as compared to patients (60-80% versus 40-70%) and believed that mortality in the general population was around 1-5% (50% versus 36%). Our findings are consistent with those found in other studies [19] , [25] , [28] , [33] , [35] .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, a higher proportion of HCWs perceived a high risk of COVID-19 as compared to patients (60-80% versus 40-70%) and believed that mortality in the general population was around 1-5% (50% versus 36%). Our findings are consistent with those found in other studies [19] , [25] , [28] , [33] , [35] .…”
Section: Discussionsupporting
confidence: 94%
“…Among the HCWs, 85% reported to use official sources for information about COVID-19, whereas 90% “patients used the media. Moreover, a systematic review by Sarria-Guzman et al [32] in the general population and several studies in HCWs [22] , [29] , [35] reported the same findings.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Bashir et al 2021 [14] reported a 26-item cross-sectional observational poll research on 597 HCWs on social media. The questionnaire was distributed randomly on Arabic-language social media platforms − the analysis from HCWs with physicians, nurses, medical students, and pharmacists as participants.…”
Section: Willingness and Preparedness Of Pharmacists To Undertake An ...mentioning
confidence: 99%
“…Whilst, nurses' experiences are a parameter that helps nurses adapt to work in a critical environment, especially they are working with confirmed cases of coronavirus patients that influence on their psychological, mental, social & interpersonal relationships Ulrich et al (2018). Healthcare providers are considered the most vulnerable to infection, exposure to many psychological stress, and physical problems as well as unexpected death, among them Bashir et al (2020). In particular, nurses play a critical role in controlling covid-19 infection Mitchell et al (2021).…”
Section: Introductionmentioning
confidence: 99%